THE INFLUENCE OF CASHBACK, FLASH SALE AND PAYLATER ON IMPULSIVE PURCHASES OF SHOPEE USERS IN LHOKSEUMAWE CITY: - Putri Dinda Pertiwi; Samsul Bahri; T. Edyansyah; Mariyudi (RADJA PUBLIKA, 2024)
The purpose of this study was to determine Cashback, Flash Sale and Paylater on impulse purchases of Shopee users in Lhokseumawe City. Data for this study were collected through a survey method using a questionnaire as a data collection instrument. The population in this study were 97 shopee users in Lhokseumawe City. Hypotheses, coefficients are determined using the SPSS version 29.0 program. The results of this study indicate that simultaneously Cashback, Flash Sale and Paylater have a significant positive effect on impulse purchases of Shopee users in Lhokseumawe City. Partially, each variable, namely Cashback, Flash Sale and Paylater , has a positive and significant effect on impulse purchases of shopee users in Lhokseumawe City. The Adjusted R Square value of 0.204 obtained by the variable can be explained by the independent variable, namely Cashback, Flash Sale, and Paylater by 20.4% while the remaining 79.6% can be explained by other variables not analyzed by this study.